Personality Type and Motivation to Play MMO Games - Daniel Kaufmann (Journal of Scholarly Engagement)
Massively Multiplayer Online Role-Playing Games (MMORPGs) consist of many qualities which relate to the World Health Organization’s decision to identify Video Game Disorder as a defined mental health condition. While structural characteristics can determine the routine patterns of behavior a player may demonstrate, other factors are often involved in the discussion of why some elements within a game would appeal to certain players when compared to others. Open-ended gaming, such as what is found in many online games, is found in past research to lead to immersive experiences which could be perceived by mental health professionals as a tendency towards the developing an addiction around certain game types. The MMORPG genre can occupy extensive amounts of time in perpetuity, which then leads to interference in other life areas when a strategy for life balance is lacking. This study aimed to find ways personality theory could expand counselors’ understanding of motivational conditions involved in the play of online video games. For this purpose, participation involved the completion of a personality assessment tool (MBTI-M) and an assessment to measure specific motivation elements for playing online games (MPOGQ) by players of the specific online game targeted for this study; Star Wars: The Old Republic (SWTOR). Significant differences across many personality types were found in most gaming motivation categories. Findings suggest personality does have an impact on the manner in which MMORPG players seek to participate in their game of choice.